Modulation‐Doped In2O3/ZnO Heterojunction Transistors Processed from Solution. Issue 19 (15th March 2017) - Khim, Dongyoon; Lin, Yen‐Hung; Nam, Sungho; Faber, Hendrik; Tetzner, Kornelius; Li, Ruipeng; Zhang, Qiang; Li, Jun; Zhang, Xixiang; Anthopoulos, Thomas D.
Abstract : This paper reports the controlled growth of atomically sharp In2 O3 /ZnO and In2 O3 /Li‐doped ZnO (In2 O3 /Li‐ZnO) heterojunctions via spin‐coating at 200 °C and assesses their application in n‐channel thin‐film transistors (TFTs). It is shown that addition of Li in ZnO leads to n‐type doping and allows for the accurate tuning of its Fermi energy. In the case of In2 O3 /ZnO heterojunctions, presence of the n‐doped ZnO layer results in an increased amount of electrons being transferred from its conduction band minimum to that of In2 O3 over the interface, in a process similar to modulation doping. Electrical characterization reveals the profound impact of the presence of the n‐doped ZnO layer on the charge transport properties of the isotype In2 O3 /Li‐ZnO heterojunctions as well as on the operating characteristics of the resulting TFTs. By judicious optimization of the In2 O3 /Li‐ZnO interface microstructure, and Li concentration, significant enhancement in both the electron mobility and TFT bias stability is demonstrated. Abstract : Modulation doping of isotype In2 O3 /ZnO heterojunction transistors fabricated from solution is demonstrated. Selective n ‐ type doping of the top ZnO layer with Li is used to improve the electron mobility and operating stability of In2 O3 /ZnO heterojunction transistors, while maintaining the processes temperature at ≤200 °C. The method is simple and potentially applicable to other material systems.